Imaginary reality - Tas-ool, Viktoria V. (The New Research of Tuva, 2010)
Work for the contest "Tuva-2050". Overview of education and science of Tuva in 2040 through a small magnifier, a sleep.
Keywords: competition; Tuva-2050; essay; foresight; youth